A comparative study of CdS thin films grown on ultra-thin glass substrates by RF magnetron sputtering and chemical bath deposition. (October 2021) - Doroody, C.; Rahman, K.S.; Rosly, H.N.; Harif, M.N.; Isah, M.; Kar, Y.B.; Tiong, S.K.; Amin, N.
Abstract: The structural, morphological and optoelectrical characteristics of cadmium sulfide (CdS) thin films grown on ultra-thin glass substrates via Radio Frequency (RF) magnetron sputtering and chemical bath deposition (CBD) have been explored in this study. CdS thin films were characterized using the X-ray Diffraction (XRD), Field Emission Scanning Electron Microscopy (FESEM), Atomic Force Microscopy (AFM), UV–Vis spectrophotometer and Hall effect measurement system. As obvious from XRD investigation, the stable hexagonal wurtzite crystalline structure with (002) preferential orientation was resulted from both deposition methods. FESEM study demonstrated uniform grain structure for the sputtered films. Compositional analysis confirmed that S/Cd ratio is 0.28 for the sputtered films and 0.20 for the CBD films. AFM study exhibited spherical crystal surface formation, hills and valleys for CBD films. The optical analysis showed a band gap of 2.40 eV and 2.32 eV for the sputtering and the CBD methods, respectively. Hall effect analysis recorded carrier concentration and resistivity in the order of 10 13 cm −3 and 10 4 Ω cm, respectively. The experimental results recommend that the CdS thin films grown by the sputtering might be favourable as the window layer for solar cell application. Highlights: CdS thin films were grown on ultra-thin glass substrates via RF magnetron sputtering and chemical bath deposition. Crystallite size was 51.08 nm for the sputtered films and 34.06 nm for the films grown by chemical bath deposition. Compositional analysis confirmed that the S/Cd ratio is 0.28 for the sputtered films and 0.20 for the CBD films. The optical analysis showed a band gap of 2.40 eV and 2.32 eV for the sputtering and the CBD methods, respectively. The experimental results recommend that the sputtered CdS thin films might be favourable as the optimum window layer.